Overtime Pay, Overtime Hours, and Labor Unions - Trejo, Stephen J. (Journal of Labor Economics, 1993)
This article analyzes the effect of labor unions on overtime compensation and overtime hours. Estimates from May 1985 Current Population Survey data indicate that unionization increases the prevalence of premium pay for overtime and reduces the incidence and extent of overtime hours. Along with the finding of previous research that unionized workers are more susceptible to temporary layoffs, these results are consistent with a model in which unions use overtime pay to stabilize working hours and expand membership.